1989
DOI: 10.1002/1097-0142(19890915)64:6<1195::aid-cncr2820640606>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in mobile tongue and floor of mouth carcinoma

Abstract: This study identifies significant prognostic factors in squamous cell carcinomas of the anterior tongue and floor of mouth. It is clear that the TMN staging system does not account for other important variables that affect tumor prognosis. Tumor thickness and the presence of perineural invasion and intralymphatic tumor emboli should be examined in all resected tumors. Tumor thickness, tumor size, and perineural invasion all have an impact on survival and must be considered in treatment plans. Tumors measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
112
1
9

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(127 citation statements)
references
References 9 publications
5
112
1
9
Order By: Relevance
“…Nor did histological differentiation have any prognostic impact, in contrast to what others have found (7, 8). Several authors have shown that tumour thickness in mm (9-1 1) and perineural infiltration (10,12,13) determined from a histological specimen, are significantly correlated with prognosis. However, to make use of these findings, planned treatment with radical surgery would have to be done without knowing the result.…”
Section: Discussionmentioning
confidence: 99%
“…Nor did histological differentiation have any prognostic impact, in contrast to what others have found (7, 8). Several authors have shown that tumour thickness in mm (9-1 1) and perineural infiltration (10,12,13) determined from a histological specimen, are significantly correlated with prognosis. However, to make use of these findings, planned treatment with radical surgery would have to be done without knowing the result.…”
Section: Discussionmentioning
confidence: 99%
“…Although the evidence is not entirely consistent across studies, on balance supports, it the importance of measuring DI and assessing LVI and PNI as part of the histologic workup for patients with newly diagnosed tongue cancer. [9][10][11][12][13][14][15][16][17][18][19][20][21] It is important to emphasize that the relation between DI and survival in our data are not consistent with a simple biologic gradient. We produced no evidence that a gradual increase in DI beyond 3 mm is associated with a further increase in mortality.…”
Section: Discussionmentioning
confidence: 94%
“…6 Similar to our analyses, the majority of previously published studies examined the effect of DI on survival by using the cutoff levels of >3 mm or 4 mm. 11,15,16,[18][19][20]22 The biologic rationale for using this particular cutoff level needs to be understood, but the consistency of results across studies is noteworthy. We also confirmed previous reports indicating the prognostic value of tumor size 11,23,24 and the lack of an association between survival and tumor grade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations